On the role of male competition in speciation: a review and research agenda. (21st December 2017) - Tinghitella, Robin M; Lackey, Alycia C R; Martin, Michael; Dijkstra, Peter D; Drury, Jonathan P; Heathcote, Robert; Keagy, Jason; Scordato, Elizabeth S C; Tyers, Alexandra M
Abstract : Little attention has been given to how males competing for mates can facilitate the evolution and persistence of new species. We expand the current framework for how new species evolve (speciation) to include male competition, drawing on recent research to show how male competition contributes to divergence between co-occurring or spatially isolated populations. We also identify interactions with female mate choice and environmental variation, and formulate a research program that will move this field forward. Abstract: Support for the role of sexual selection in speciation has grown over the last 30 years. Work in this area, however, has largely focused on a single dominant question: when and how do divergent male sexual signals and corresponding female preferences lead to reproductive isolation? The field has not given adequate attention to the role that male competition, Darwin's second mechanism of sexual selection, might also play in speciation. In this review, we summarize recent work that shows precopulatory male competition can initiate speciation in sympatry, drive divergence of competitive phenotypes in allopatry, and strengthen reproductive barriers between competitive types during secondary contact. The manner by which male competition contributes to divergence in allopatry is a poorly understood yet compelling area of research; similar to female choice, male competition may be more likely to lead to speciation when working in concert with divergent ecology, and allopatry sets the stage for divergence among environments with reduced gene flow. To encourage future research in this area, we place potential mechanisms for speciation by male competition into existing speciation frameworks and propose a theoretical and empirical research agenda to reveal how male competition contributes to the accumulation of reproductive isolation. Our current understanding of when and how divergence in competitive phenotypes leads to reproductive isolation is limited, and theoretical work may be particularly well-suited to reveal when divergence by male competition is fastest and most likely.